PENGARUH ETOS KERJA DAN PEMBERIAN KOMPENSASI TERHADAP KINERJA DOSEN DAN PEGAWAI DI LINGKUNGAN IAIN PADANGSIDIMPUAN - Rukiah Rukiah (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2016)
This study determine whether there is influence of moslem’s work ethic and com-pensation to the performance of IAIN Padangsidimpuan’s lecturers and staff and how big the influences are. The research is a quantitative explainatory, data col-lected using a questionnaire with sample 36 lecturers and employees. Results from the study showed a significant effect among moslem’s work ethic and the compensation to the performance, shown by R = 0.777. This means that indepen-dent variables are able to explain the dependent variable of 0.777 or 77.7% while the remaining 22.3% is explained by other variables outside the model. While tests of significance can be seen from the t test, moslem’s work ethic affect the performance of t-count t-table or 4,623 1,691 and 0,00 0,05, and compensa-tion affect the performance of t-count t-table or 4,455 1,691 and 0,00 0,05 , means moslem’s work ethic and compensation in the form of certified lecturers and remuneration have a significant effect on performance.